Advanced glycation end products (AGEs) and their receptor (RAGE) induce apoptosis of periodontal ligament fibroblasts - Li,D.X. (2014)
Diabetics have an increased prevalence of periodontitis, and diabetes is one of the causative factors of severe periodontitis. Apoptosis is thought to be involved in this pathogenic relationship. The aim of this study was to investigate apoptosis in human periodontal ligament (PDL) fibroblasts induced by advanced glycation end products (AGEs) and their receptor (RAGE). We examined the roles of apoptosis, AGEs, and RAGE during periodontitis in diabetes mellitus using cultured PDL fibroblasts that were treated by AGE-modified bovine serum albumin (AGE-BSA), bovine serum albumin (BSA) alone, or given no treatment (control). Microscopy and real-time quantitative PCR indicated that PDL fibroblasts treated with AGE-BSA were deformed and expressed higher levels of RAGE and caspase 3. Cell viability assays and flow cytometry indicated that AGE-BSA reduced cell viability (69.80±5.50%, P<0.01) and increased apoptosis (11.31±1.73%, P<0.05). Hoechst 33258 staining and terminal-deoxynucleotidyl transferase-mediated nick-end labeling revealed that AGE-BSA significantly increased apoptosis of PDL fibroblasts. The results showed that the changes in PDL fibroblasts induced by AGE-BSA may explain how AGE-RAGE participates in and exacerbates periodontium destruction.